Ocular immunology - Bąkowska, Alicja (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
In this paper, some aspects of ocular immunological defence with particular consideration of regional immunity are reviewed. It is discussed the lacrimal drainage associated lymphoid tissue (LDALT) and unique factors determinating the eye as an immunologically “privileged” organ (blood-ocular barrier, sequestration of antigens, absence of lymphatic draining, ocular microenvironment modulating the immunity).